Framing Canadian federalism : historical essays in honour of John T. Saywell - Saywell, John T., 1929-2011; Bryden, Penny; Anastakis, Dimitry, 1970- (University of Toronto Press, 2009)
"Framing Canadian Federalism assembles an impressive range of scholars to consider many important issues that relate to federalism and the history of Canada's legal, political, and social evolution. Covering topics such as the Supreme Court of Canada, changing policies towards human rights, First Nations, as well as the legendary battles between Mitchell Hepburn and W.L. Mackenzie King, this collection illustrates the central role that federalism continues to play in the Canadian polity."--Pub. desc